Current management of acute ischemic stroke. Part 2: Antithrombotics, neuroprotectives, and stroke units. - Herd, A. M. (2001)
OBJECTIVE: To help family physicians who care for patients with acute stroke or who are involved in planning service delivery or resource allocation to understand recent developments in acute stroke care. QUALITY OF EVIDENCE: A MEDLINE search indicated that most data were derived from well designed, randomized, double-blind, placebo-controlled trials, including all the largest international studies and large systematic reviews. MAIN MESSAGE: Routine anticoagulation is not recommended except for circumstances such as cardioembolic stroke or deep vein thrombosis prophylaxis. Antiplatelet therapy with low-dose acetylsalicylic acid (or another antiplatelet agent if ASA is contraindicated) should be initiated within 48 hours of stroke onset, although benefit is modest. Dedicated care for stroke patients reduces morbidity and mortality and can be cost effective. Recent research into defibrinogenating and neuroprotective agents suggests some benefit, although none are currently licensed for use. Combination therapy might be the answer. CONCLUSION: Management of acute stroke is an emerging discipline; many potential therapies are still experimental.